Development and Utilization of Yellow River Resources under the Background of Sustainable Development from the Perspective of Ecology - Dafeng Xu, Haiyun Sun (Forest Chemicals Review)
As the ecological protection and high-quality development of the Yellow River Basin becomes a major national strategy, cities along the Yellow River are facing huge development opportunities. How to develop and utilize the Yellow River resource rationally in a sustainable development context, specially under the perspective of ecology, has become an urgent topic of research. Based on a traditional Analytic Hierarchy Process (AHP), this paper introduces entropy analysis into the quantitative model, quantitatively analyzes the main factors affecting the development and utilization of resources in Ji’nan, and constructs a production function model with the endowment of Yellow River resources. The study found that the exploitability and utilizability of the Yellow River landscape rank first and second respectively, which shows that the existing Yellow River landscape in Ji’nan is not enough to support its whole Yellow River resource utilization and development strategy. It is worth noting that the research and development of the Yellow River Basin and the harmony between man and nature rank fourth and fifth respectively, which fully illustrates the development trend of giving priority to ecological development and scientific and technological innovation. The conclusion is drawn that Jinan should attach importance to promoting the economic model of ecological priority and green development in the process of resources exploitation and utilization in the Yellow River basin. Since AHP is still a subjective analysis method, how to introduce a more objective quantitative model in future research is a research direction worthy of in-depth discussion.